Effect of iron and ascorbic acid addition on dry infusion process and final color of pumpkin tissue - Genevois, Carolina Elizabeth (2014)
In the present study, pumpkin (Cucurbita moschata Duchesne ex Poiret) was used as raw material to produce sweet food fortified with iron (Fe) and ascorbic acid (AA). A dry infusion process with a subsequent air drying was applied. Response surface methodology was performed in order to analyze the effect of Fe and AA incorporation into the formulation on: water loss (WL) and solid gain (SG) during the dry infusion process, color changes (ΔE) and the dehydration percentage during subsequent air drying process. The results showed that the presence of Fe and/or AA promoted SG and WL during the dry infusion and also, weight changes during the air drying process (PP). An increase of the color changes was also observed. In turn, it was possible to obtain predictive equations for the parameters studied. The application of edible coating based on tapioca starch on pumpkin product was also tested showing a protective effect from the pumpkin color view point.